The Prevalence And The Molecular Patterns Of Rotaviruses In Calves - Tan , Esther Siew Choo (1992)

(untitled)
A study was conducted to determine the prevalence of rota virus in calves in Malaysia. A total of 977 faecal specimens were collected over a four-month period from calves starting from 48 hours. The faeces were collected from diarrhoeic as well as non-diarrhoeic calves. Four hundred samples were collected from calves in Kluang, Johore Bahru and Selangor whilst another 577 were from 23 calves from the Beef Unit, Universiti Pertanian M alaysia. The faecal specimens were analysed for the presence of rotavirus by several methods, that is, electron microscopy (EM), polyacrylamide gel electrophoresis (PAGE) and a commercial enzyme-linked immunosorbent assay (ELISA) kit - Rotazyme II. Bacteriological examination was also carried out on these specimens. Electron microscopy studies demonstrated rotaviruses in 69 (7. 1 %) of the total faecal specimens of 977, 50 from loose and 19 from non-diarrhoeic faeces. Seventy two percent of these were detected in calves less than three months old. Parvovirus or enteroviruses were also observed in 32 other diarrhoeic faecal samples. However, no coronavirus or pathogenic bacteria were detected. Studies by PAGE showed that 97 (9.9%) specimens contained rotaviruses. Thirty two percent (72%) of the positive specimens were from non-diarrhoeic and the remaining percentage (28%) were from loose specimens. All of the rotavirus isolates belonged to the group A "long" electrophoretic pattern. None had unusual segment rearrangement or possessed extra segments. Majority (62%) of the genome electropherotypes belonged to the class of Ib lIa IlIb IVa. Two isolates were found to have a variant of the 11 th segment. A total of 82 specimens (8. 4%) were found to be positive for rotavirus by ELISA. Fifty five percent of the loose calves gave strong reactions whereas 10% of the non-diarrhoeic animals gave similar reactions. These diagnostic tests revealed that there was an association between diarrhoeic specimens and higher amounts ' of rotavirus antigen. The detection of rotaviruses in the non-diarrhoeic animals indicated that sub-clinical infections were present.